Characteristics of PMMA-grafted natural rubber doped with LiCF3S03 - Yap, K.S.; Teo, L.P.; Sim, L.N.; Majid, S.R.; Arof, Abdul Kariem (2009)
Varying ratios of polymer electrolyte films containing MG30 doped with LiCF3S03 were prepared using the solution casting method. Pure MG30 with 30 wt. % LiCF3S03 was found to exhibit the highest conductivity at 5.62 x 10-8 S cm' at ambient emperature. Analyses by X-ray diffraction (XRD), scanning electron microscope (SEM), fourier transform infrared (FTIR) spectroscopy and electrochemical impedance spectroscopy (EIS) have been carried out to investigate the interaction between the polymer and salt.